Effect of Liquidity and Solvency on Profitability of Banking Companies in Indonesia - Hariatih Hariatih; Indrawan Aziz (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the effect of liquidity and solvency on profitability as one of the company's main objectives. The population in this study was 36 banks listed on the Indonesia Stock Exchange for the period 2014-2018. This research was conducted using secondary data from the Indonesia Stock Exchange (IDX). Sample selection was made using the purposive sampling technique. Of the 36 banks listed on the Indonesia Stock Exchange, ten have had a positive profitability trend in the last four years. The type of data used in this research is quantitative data. The data was obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id, in the form of quarterly financial reports (March 2014-September 2018). Go public, commercial banks. The data collection technique used in this research is the method of documentation analysis or literature study. The results obtained are 1) Liquidity variable (LDR) has a positive and significant effect on the profitability (ROE) of banks listed on the Indonesia Stock Exchange. 2) Solvency variable (DER) has no (negative) and no significant effect on the profitability (ROE) of banks listed on the Indonesia Stock Exchange. 3) Liquidity (LDR) and Solvency (DER) variables have a significant positive effect on the profitability (ROE) of banks listed on the Indonesia Stock Exchange.